The Effectiveness of Remineralization with Compound Silver Nanoparticles and Fluoride Varnish in Carious Lesions in Primary Teeth: A Randomized Split-Mouth Clinical Trial - María Lilia Adriana Juárez-López; Miriam Marín-Miranda; Rosita Palma-Pardínes; Raquel Retana-Ugalde (MDPI AG, 2024)
Background: Anti-cariogenic properties of silver nanoparticles and fluorides have been probed mainly in vitro and with the objetive to evaluate the remineralizing effects of an applied silver nanoparticle compound plus fluoride varnish, a randomized split-mouth clinical trial was conducted in children aged 6 to 7 years. Methods: The project was approved by the ethics committee of the faculty. Primary molars were randomly distributed into two groups, as follows: Group A was treated with a compound based on silver nanoparticles plus fluoride varnish (SNP-FV), and Group B was treated with a silver diamine fluoride compound (SDF-KI), which is the current standard treatment. Laser fluorescence with a DIAGNOdent pen was used for the evaluation, with follow-up examinations at 15 days, 6 months, and 12 months. ANOVA test was used to compare the groups. The results showed a decrease in demineralization was observed after treatment with SNP-FV; similar results were observed after treatment with SDF-KI. Within each group, there were favorable changes. In the SDF-KI group, the differences in demineralization were 25.63 at 15 days, 29.37 at 6 months, and 30.6 at one year (p < 0.05). Meanwhile, in the SNP-FV group, the decreases were 22.7 at 15 days, 28.78 at 6 months, and 31.11 at one year (p < 0.05). Conclusions: The SNP-FV combined treatment represents an alternative remineralizing treatment for the management of carious lesions in the dentin of primary molars.